Electrochemical Modeling and Performance of a Lithium- and Manganese-Rich Layered Transition-Metal Oxide Positive Electrode. Issue 4 (21st January 2015) - Dees, Dennis W.; Abraham, Daniel P.; Lu, Wenquan; Gallagher, Kevin G.; Bettge, Martin; Jansen, Andrew N.
Abstract : The impedance of a lithium- and manganese-rich layered transition-metal oxide (LMR-NMC) positive electrode, specifically Li1.2 Ni0.15 Mn0.55 Co0.1 O2, is compared to two other transition-metal layered oxide materials, specifically LiNi0.8 Co0.15 Al0.05 O2 (NCA) and Li1.05 (Ni1/3 Co1/3 Mn1/3 )0.95 O2 (NMC). A more detailed electrochemical impedance spectroscopy (EIS) study is conducted on the LMR-NMC electrode, which includes a range of states-of-charge (SOCs) for both current directions (i.e. charge and discharge) and two relaxation times (i.e. hours and one hundred hours) before the EIS sweep. The LMR-NMC electrode EIS studies are supported by half-cell constant current and galvanostatic intermittent titration technique (GITT) studies. Two types of electrochemical models are utilized to examine the results. The first type is a lithium ion cell electrochemical model for intercalation active material electrodes that includes a complex active material/electrolyte interfacial structure. The other is a lithium ion half-cell electrochemical model that focuses on the unique composite structure of the bulk LMR-NMC materials.